2003
DOI: 10.1542/peds.111.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration From Infancy to Adolescence: Reference Values and Generational Trends

Abstract: Percentile curves provide valuable information on developmental course and age-specific variability of sleep duration for the health care professional who deals with sleep problems in pediatric practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

79
779
23
45

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,153 publications
(926 citation statements)
references
References 19 publications
79
779
23
45
Order By: Relevance
“…This is in line with previous studies that reported sleep duration became shorter during adolescence (Fallone et al, 2002;Iglowstein et al, 2003). Variation in sleep duration was accounted for by genetic, shared environmental, and non-shared environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies that reported sleep duration became shorter during adolescence (Fallone et al, 2002;Iglowstein et al, 2003). Variation in sleep duration was accounted for by genetic, shared environmental, and non-shared environmental factors.…”
Section: Discussionsupporting
confidence: 92%
“…The average sleep durations in the present study, as categorized by age, were lower than the US references 33 and the recommendations of the Chinese government (at least 10 h for children <10 years old, 9 h for 11-14 years old, and 8 h for >15 years old).…”
Section: Discussioncontrasting
confidence: 82%
“…BP was classified using the population-based percentiles. 32,33 Normal BP was defined as SBP and/or DBP <90th percentile for age, sex, and height; prehypertension was defined as SBP and/or DBP 90th and <95th percentile for age, sex, and height, or if the SBP was more than 120 mmHg or DBP was more than 80 mmHg. Hypertension (HTN) was defined as SBP and/or DBP 95th percentile.…”
Section: Blood Pressurementioning
confidence: 99%
“…Brain activity resembling that of SWS begins to emerge in the first few months of life (Sheldon 2005b), and the proportion of SWS is greatest during childhood than in any other period in life, which reduces by approximately 40% during adolescence (Carskadon and Dement 2011), highlighting the potential importance of sleep on maturational processes and the growth of new connections. The infant sleep period of an average 17--19 hours per day gradually reduces to around 8--9 hours by adolescence (Iglowstein et al 2003, and see Figure 1 for sleep stage changes across the lifespan).…”
mentioning
confidence: 99%